Studi Perbedaan Efektivitas Model Pembelajaran Kooperatif Tipe Jigsaw dan Snowball Throwing terhadap Prestasi Belajar Matematika Siswa Kelas VIII SMPN 1 Narmada - Nurbaeti Irmayani; Ketut Sarjana; Eka Kurniawan; Nyoman Sridana (Griya Journal of Mathematics Education and Application, 2021)
This research aims to find out whether there are differences in students' mathematics learning outcomes using the Jigsaw type cooperative learning model, with the Snowball throwing type cooperative learning model in VIII class of SMPN 1 Narmada. This type of research is an experimental. The sample class was selected using the random sampling cluster technique, with class VIII 1 was obtained as an experimental class with the Jigsaw model and VIII 2 as an experimental class with the Snowball Throwing model. The data was collected using students‟ achievement test as the instrument. The post-test with independent sample t test at the significance level 5% yields thitung>ttabel that is 2,773>1,993 which means that there is a difference between classes taught by Jigsaw and Snowball Throwing toward students' achievement on mathematics at the VIII grade students of SMPN 1 in the academic year 2019/2020. The result shows that the second experimental class obtain higher score (88,24) than the first experimental class (81,21).